Correction: Oligonucleotide-templated lateral flow assays for amplification-free sensing of circulating microRNAs. Issue 89 (24th October 2019) - Pavagada, Suraj; Channon, Robert B.; Chang, Jason Y. H.; Kim, Sung Hye; MacIntyre, David; Bennett, Phillip R.; Terzidou, Vasso; Ladame, Sylvain
Abstract : Correction for 'Oligonucleotide-templated lateral flow assays for amplification-free sensing of circulating microRNAs' by Suraj Pavagada et al., Chem. Commun., 2019, 55, 12451–12454.